Design and efficiency optimization of off-grid solar-wind hybrid power systems in Bahuluang tourism village - Hidayat, Akmal; Mudarris, Mudarris; Fakhri, M. Miftach; Iriandy, Iriandy; Rahman, M. Haristo (Politeknik Negeri Lhokseumawe, 2025)
Access to reliable and sustainable energy remains a critical challenge in remote regions, limiting socio-economic growth and the development of tourism-based communities. In line with Indonesia’s Net Zero Emissions (NZE) targets and national energy equity initiatives, this study explores the planning and efficiency optimization of a Hybrid Renewable Energy System (HRES) for Bahuluang Tourism Village. The proposed off-grid system integrates wind turbines, solar Photovoltaic (PV) panels, and battery storage to minimize fossil fuel dependence and environmental impact. Using literature review and simulation-based analysis with HOMER software, the study identifies an optimal configuration comprising 172.77 kW of solar PV, 36.82 kW of wind turbines, 98 batteries (1.2 kWh each), and a 50-kW inverter. The system generates approximately 209,851 kWh annually—82.4% from wind and 17.6% from solar—efficiently meeting the local demand of 424.1 kWh per day. This hybrid system supports sustainable energy access, reduces carbon emissions, and promotes the energy transition in line with Indonesia’s clean energy goals.